Asuhan Kebidanan Komprehensif Pada Ny. F Umur 30 Tahun Dengan Presentasi Bokong di Wilayah Kerja Puskesmas Bumiayu Kabupaten Brebes Tahun 2023 - Alfi Nur Maulida; Himatul Khoeroh; Uma Cholifah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Agreeing to the World Wellbeing Organization (WHO), around 810,000 ladies passed on due to complications related to pregnancy or childbirth all through the world, the MMR in Indonesia as of 2022 is 305/100,000 live births, WHO information for 2021 states that the Newborn child Mortality Rate (IMR) within the world is 235 passings per 100,000 live births. Brebes Wellbeing Office (2022) MMR 50 cases, IMR 259 cases. Information from Bumiayu Community Wellbeing Center (2022) AKI 2 cases, 14 cases. This analyst is able to carry out comprehensive birthing assistance care for Mrs. F 30 a long time ancient with breech introduction utilizing Varney's seven-step obstetric administration and Cleanser. Based on the foundation over, the problem formulation is how to supply comprehensive maternity care care for Mrs. F 30 a long time ancient at BPM Mrs. U work range of Bumiayu Community Wellbeing Center, Brebes Rule in 2023. The inquire about plan utilized by the creator is subjective clear inquire about. Based on the research result, it may be concluded that: Comprehensive Care for Mrs. F found issues at the starting of pregnancy with breech introduction and at the end of pregnancy no issues were found within the third trimester of pregnancy. The conveyance was carried out by caesarean segment, and the infant was ordinary. Amid the postpartum period, the uterine involution prepare goes well. Through this Logical Composing, it is trusted that wellbeing center wellbeing laborers can keep up and progress the quality of wellbeing administrations in understanding with benefit guidelines and the application of hypothesis.